Analysis of the sponsorship activities of the Organizing committee «Kiev City marathon – 2014» - Ярмолюк Олена Володимирівна, (Olena Yarmolyuk); Золотарьова Ганна Олександрівна, (Anna Zolotaryova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to share the experience of the marketing technologies application in the physical culture and sports sphere and to improve the commercial activities of sports organizations during the planning and holding the mass sporting events. Material and Methods: the basic forms and methods of the sponsorship activities of the Organizing Committee of the competition «Kiev Marathon – 2014» were analyzed with system analysis, SWOT-analysis and sociological questioning (12 specialists from the Organizing Committee of «Kiev City Marathon – 2014» and 95 visitors of the «Kiev City Marathon – 2014» were questioned). Results: the best way for obtaining the sponsorship is to use the level-approach by the organizers, which means that all sponsors were divided on different levels and each one had certain privileges. It had resulted in appropriate sponsorship agreements. Conclusions: the results of research given in the article will enable professionals to most effectively search and work with the sponsors in the physical culture and sports sphere, as well as to introduce modern mechanisms of interaction between businesses and sporting organizations.